Hamiltonian formulation for the motion of a two fluid system with free surface - Sciortino, G.; M.La Rocca; Boniforti, M. (Нелінійні коливання, 2003)
In this work a theoretical investigation is performed on modeling interfacial and surface waves in a layered
fluid system. The physical system consists of two immiscible liquid layers of different densities ρ1 > ρ2
with an interfacial and a free surface, inside a prismatic-section tank. By using the potential formulation of
the fluid motion, a nonlinear system of partial differential equations is derived applying an Hamiltonian
formulation for irrotational flow of the two fluids of different density subject to conservative force. As a
consequence of the assumption of potential velocity, the dynamics of the system can be described in terms
of variables evaluated only at the boundary of the fluid system, namely the separation surface and the
free surface. This Hamiltonian formulation permits to define the evolution equations of the system in a
canonical form by using the functional derivatives. Виконано теоретичне моделювання внутрiшнiх та поверхневих хвиль у шаровiй системi рiдин.
Фiзична система складається з двох рiдин, що не змiшуються, рiзних щiльностей ρ1 > ρ2 з
внутрiшньою та вiльною поверхнями в призматичному бацi. На основi потенцiалу руху рiдини за допомогою гамiльтонового пiдходу до безвихрової течiї двох рiдин рiзної щiльностi пiд
дiєю консервативної сили отримано нелiнiйну систему диференцiальних рiвнянь з частинними похiдними. Як наслiдок припущення про наявнiсть потенцiалу швидкостi динамiка системи
описується за допомогою змiнних, заданих лише на межi системи рiдин, тобто на поверхнi розподiлу та вiльної поверхнi. Такий пiдхiд дав можливiсть визначити еволюцiйнi рiвняння системи
в канонiчнiй формi за допомогою функцiональних похiдних.